The Critical Role of Leadership in Patient Safety Culture: A Mediation Analysis of Management Influence on Safety Factors - Huang CH; Wu HH; Lee YC; Li X (Dove Medical Press, 2024)
Chih-Hsuan Huang,1- 3 Hsin-Hung Wu,4,5 Yii-Ching Lee,6 Xiumei Li1 1Business School, Hubei University of Economics, Wuhan City, People's Republic of China; 2Hubei Enterprise Culture Research Center, Hubei University of Economics, Wuhan, People's Republic of China; 3Research Center of Hubei Logistics Development, Hubei University of Economics, Wuhan, People's Republic of China; 4Department of Business Administration, National Changhua University of Education, Changhua City, Taiwan; 5Faculty of Education, State University of Malang, Malang, East Java, Indonesia; 6Department of Health Business Administration, Hung Kuang University, Taichung City, TaiwanCorrespondence: Yii-Ching Lee, Department of Health Business Administration, Hung Kuang University, No. 34 Zhongqi Road, Shalu District, Taichung City, Taiwan, Tel +886-4-26318652, Email yiiching.lee@sunrise.hk.edu.twPurpose: This research aims to investigate the role of management leadership in promoting a culture of patient safety within healthcare organizations. Through a comprehensive mediation analysis of the Chinese version of the safety attitudes questionnaire (CSAQ) and patient safety culture, the study examines the interplay between these critical factors and their combined influence on healthcare outcomes.Patients and Methods: In a medical center located in Taiwan, a cross-sectional survey was carried out utilizing the CSAQ. Among the 1500 distributed surveys, 1037 were returned and deemed valid, resulting in a return rate of 69.13%. To investigate the main measures, Structural Equation Modeling with mediation analysis was employed to scrutinize the direct and indirect effects of factors including teamwork climate, job satisfaction, stress recognition, perceptions of management, working conditions, and emotional exhaustion on safety climate.Results: The findings reveal that effective management leadership plays a pivotal role in shaping safety attitudes and fostering a robust patient safety culture. The study identifies three critical facets of patient safety that are entirely mediated by management perceptions: teamwork climate, working conditions, and stress recognition. The results highlight the importance of enhancing these dimensions to advance the patient safety culture within healthcare organizations. Moreover, stress recognition is identified as a critical factor influencing the organizational culture of patient safety.Conclusion: This research offers valuable insights for healthcare organizations seeking to prioritize patient safety and improve overall quality of care. By enhancing our understanding of the critical factors that shape safety attitudes and patient safety culture, this study provides a roadmap for effective management leadership and a culture of patient safety within healthcare organizations. The study underscores the significance of management leadership in promoting patient safety culture and highlights the importance of enhancing teamwork climate, working conditions, and stress recognition to advance patient safety culture.Keywords: management leadership, safety attitudes questionnaire, patient safety culture, mediation effect